Desempenho de cultivares de algodão em Alegrete Rio Grande do Sul - Silva, Airam Fernandes da (2012)
Cotton (Gossypium hirsutum L. race latifolium Hutch.) is a crop cultivated in several regions of Brazil and the world, detached in the global agribusiness because of the use of their products and sub-products. Similarly as it happened in the Brazilian Cerrado, cotton crop may be an alternative of production for rotation in areas with soybeans and corn in Rio Grande do Sul, associated to the climatic conditions and utilization of high technology and management that upgrade the product and crop handling. Objecting to prevent new necessities and to anticipate new technologies, it was verified the productivity and seed physiological quality and fiber quality of cotton cultivars in Alegrete, West of Rio Grande do Sul state. The experiment was conducted for two years, at the Instituto Federal de Educação, Ciência e Tecnologia Farroupilha Campus Alegrete, during 2010/11 and 2011/12 crop seasons. The experimental design was casualized blocks with five replications. The experimental data were submitted to analysis of variance, being the treatment effects evaluated by the F test, while averages were compared by the Duncan test to 5% significance. It was concluded that cotton cultivars studied produced high physiological quality seeds and fiber quality with inert characteristics considered outstanding. There are differences of performance in production and seed physiological quality among cultivars, influenced by regional climatic characteristics of the crop. The region of Alegrete, Rio Grande do Sul, has favorable climate to produce cotton seeds of high physiological quality.